Differentiation between multiple sclerosis and neuromyelitis optica spectrum disorder using optical coherence tomography angiography - Małgorzata Rogaczewska; Sławomir Michalak; Marcin Stopa (Scientific Reports, 2021)
Abstract Neuromyelitis optica spectrum disorder (NMOSD) and multiple sclerosis (MS) are autoimmune demyelinating diseases of distinct etiology presenting with optic neuritis (ON). This study aimed to identify the macular and peripapillary neurovascular alterations that may facilitate the differentiation between NMOSD and MS eyes using spectral-domain optical coherence tomography (OCT) and OCT angiography (OCTA). A total of 13 NMOSD patients and 40 MS patients were evaluated. After ON, the radial peripapillary capillary (RPC) vessel density was significantly decreased in the superior (S) and inferior (I) sectors in NMOSD compared with MS eyes, whereas in non-ON eyes, the temporal (T) sector of RPC was reduced in MS group. In the ON eyes, the retinal nerve fiber layer in the I and T quadrants was thinner in NMOSD than in MS. Regarding ON and non-ON eyes, the macular capillary plexuses, and the ganglion cell complex thickness did not differ between NMOSD and MS. The ratios, based on the disease-specific intra-eye RPC vessel density reduction pattern, were the best discriminants between NMOSD and MS, i.e., inferior to nasal (I/N) and I/T ratios for ON eyes, and S/T and N/T ratios for non-ON eyes. Our results show that the OCTA-based simple ratios may be useful in distinguishing NMOSD and MS patients.